Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12887-019-1711-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased liver echogenicity and liver enzymes are associated with extreme obesity, adolescent age and male gender: analysis from the German/Austrian/Swiss obesity registry APV

Abstract: Background Childhood obesity is often associated with non-alcoholic fatty liver disease (NAFLD), the most common chronic liver disease in pediatrics. Methods This multi-center study analyzed liver echogenicity and liver enzymes in relation to obesity, age, gender and comorbidities. Data were collected using a standardized documentation software (APV) from 1.033 pediatric patients (age: 4–18 years, body mass index = BMI: 28–36 kg/m2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
2
14
2
Order By: Relevance
“…In accordance with other studies [15,16], the present study found a dose-response association between the degree of obesity and increased ALT among children and adolescents with obesity. Moreover, we have been able to show that the dose-response association is stronger in markedly increased ALT compared to mildly increased ALT.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In accordance with other studies [15,16], the present study found a dose-response association between the degree of obesity and increased ALT among children and adolescents with obesity. Moreover, we have been able to show that the dose-response association is stronger in markedly increased ALT compared to mildly increased ALT.…”
Section: Discussionsupporting
confidence: 93%
“…Although several studies have investigated the association of elevated ALT with age and sex among children and adolescents with obesity [15,16,33], previous studies did not take sex-age interaction into account in the analyses. The present study confirms that both sex and age are independently associated with elevated ALT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of NAFLD is highly dependent on age, gender and ethnicity [4]. Fatty liver in adolescents is more common than in young children and is twice more frequent in boys than in girls [5,6]. Unfortunately, despite considerable progress in understanding the complexity of the disease, the pathophysiological mechanisms involved in the onset and progression of liver damage in paediatric NAFLD remain unclear [2].…”
Section: Introductionmentioning
confidence: 99%